A cross sectional study on needle stick and sharp injuries among health care providers in tertiary centers, Tamil Nadu - P. A., Archana Lakshmi; Raja, Ashrof; Stanly A., Meriton; Mary Paul, Christina; H., Gladius Jennifer (International Journal Of Community Medicine And Public Health, 2018)
Background: Health care workers are at risk of acquiring life threatening blood borne infections through needle stick and sharp injuries (NSSI) in their work place. This study was planned to highlight some important factors responsible for NSSI and possible measures to reduce it. The objective of the study was to assess the factors associated with NSSI and reasons for under-reporting. Methods: A cross sectional study was done during November 2014 to April 2015 in two tertiary health care institutions. All health care providers (Doctors, nurses and lab technicians) who had more than one year experience and gave informed consent were included. Data collected by pretested structured questionnaire. Data analysis was done using SPSS 20v and summarized by descriptive statistics. Proportion and Chi-square was calculated at 5% α. Results: Among 950 health care providers (HCPS), 649 (68.3%) had NSSI during their carrier, 335 (35.3%) in last one year. Females 225 (67.2%) experienced more NSSI. This study shows that, 98 (29.3%) HCPs had sustained injury once. Among the doctors, 51.4% Anaesthetist (p=0.001) and its more among the nurses (38.4%) followed by doctors (36.6%) (p=0.002). NSSI was more common among HCP who work between 30-40 hrs (p=0.00001). Majority of them sustained injury while performing the procedure 134 (40%), commonest place of injury was OT 149 (44.5%) and commonest item responsible was hypodermic needle 141 (42.1%). Only 50 (14.9%) reported to the concerned authority and follow up action was taken. Conclusions: The study shows high prevalence of NSSI, emphasizing the need for safe measures for handling sharps to prevent transmission of infection.